Rad51 suppresses gross chromosomal rearrangement at centromere in Schizosaccharomyces pombe - Nakamura, Ken-ichi (Nature Publishing Group, 2008)
Centromere that plays a pivotal role in chromosome segregation is composed of repetitive elements in many eukaryotes. Although chromosomal regions containing repeats are the hotspots of rearrangements, little is known about the stability of centromere repeats. Here, by using a minichromosome that has a complete set of centromere sequences, we have developed a fission yeast system to detect gross chromosomal rearrangements (GCRs) that occur spontaneously. Southern and comprehensive genome hybridization analyses of rearranged chromosomes show two types of GCRs: translocation between homologous chromosomes and formation of isochromosomes in which a chromosome arm is replaced by a copy of the other. Remarkably, all the examined isochromosomes contain the breakpoint in centromere repeats, showing that isochromosomes are produced by centromere rearrangement. Mutations in the Rad3 checkpoint kinase increase both types of GCRs. In contrast, the deletion of Rad51 recombinase preferentially elevates isochromosome formation. Chromatin immunoprecipitation analysis shows that Rad51 localizes at centromere around S phase. These data suggest that Rad51 suppresses rearrangements of centromere repeats that result in isochromosome formation.